Think Pair Share sebagai Model Pembelajaran Kooperatif untuk Peningkatan Kemampuan Pemecahan Masalah Matematis - Syintia Siti Latifah; Irena Puji Luritawaty (Institut Pendidikan Indonesia, 2020)
AbstrakDiperlukan upaya untuk meningkatkan pencapaian kemampuan pemecahan masalah matematis yang masih rendah, misalnya menggunakan model pembelajaran tipe Think Pair Share. Tujuan penelitian yaitu mengetahui peningkatan dan seberapa jauh kemampuan pemecahan masalah matematis siswa dapat meningkat dengan model pembelajaran Think Pair Share. Metode penelitian yaitu kuasi eksperimen, dengan populasi siswa kelas VIII di satu SMP di Kabupaten Garut. Sampel yaitu kelas VIII-A sejumlah 33 siswa, dipilih berdasarkan teknik purposive sampling. Instrumen berupa soal tes uraian kemampuan pemecahan masalah diujikan sebelum dan sesudah pembelajaran. Hasil analisis data pada kelas Think Pair Share menunjukkan peningkatan kemampuan pemecahan masalah matematis berkategori sedang. Pembelajaran kooperatif tipe Think Pair Share terbukti cukup efektif meningkatkan kemampuan pemecahan masalah matematis siswa. Think Pair Share Type Cooperative Learning Model to improve Mathematical Problem Solving Ability AbstractEfforts are needed to improve the achievement of mathematical problem-solving abilities that are still low, for example using the Think Pair Share type of learning model. The purpose of this research is to find out how much improvement and how much the students' mathematical problem-solving ability increases through the Think Pair Share learning model. The research method is quasi-experimental, with a population of eighth-grade students in one junior high school in Garut Regency. The sample is class VIII-A with 33 students, selected based on purposive sampling technique. Instruments in the form of test questions describing problem-solving abilities were tested before and after learning. The results of data analysis in the Think Pair Share class showed an increase in the ability to solve mathematical problems in the medium category. Cooperative learning Think Pair Share type proved effective enough to improve students' mathematical problem-solving abilities.